Termo-estabilização da blenda PLA/PBAT - Silva, Rafael Soares (2016)
This study aimed to evaluate the effects of additives (primary and secondary antioxidants) in thermal stabilization process of poly (lactic acid) / poly (butylene adipate-co-terephthalate) - PLA / PBAT using a torque rheometer as a preliminary tool evaluation of the stabilization process. The additives Irganox 1010, Irganox 1076, Irganox B900, Irgafos 168, and a flavonoid were used in two concentrations, 0.3 and 0.5% w/w. The assessment of the effects of stabilizing additives was carried out by monitoring the torque during mixing molar mass measurements, infrared analysis, turbidity and Scanning Electron Microscopy of the samples after processing. It carried out the monitoring of the pure blend torque values and addition of stabilizing additives during processing up to 5 minutes in an internal mixer of the type "mixer" under rotation of 60 rpm and a temperature of 180 °C. Within a series of primary and secondary antioxidants, it was found that some of these additives failed torque values greater than or similar to the pure blend at certain concentrations (Irganox 1076, Irganox B900 and Irgafos 168). molar mass measurements showed that pure processed blend undergoes a large number of chain scission and most additives stabilizing action achieved unless the flavonoid. One important information obtained through analyzes of torque rheometry and molar mass that is higher drying time strongly prevents hydrolysis reactions. Comparing the infrared spectra of pure and pure blend blend processed, there is not the appearance of no new peak occurs due to the degradative process. By UV-Vis analysis of the polymer solutions we verified the presence of crosslinked polymer microstructures due to thermo-oxidative reactions. Images obtained by scanning Elletrônica Microscopy (SEM), one can observe the presence of two distinct phases for the pure blend processed, and the use of additives in both compositions show a much smaller difference of phases to blend pure. These results indicate the possibility of using commercial additives used for non-biodegradable polymers in systems using biodegradable polymers.